Evaluation of the diagnostic accuracy of two point-of-care tests for COVID-19 when used in symptomatic patients in community settings in the UK primary care COVID diagnostic accuracy platform trial (RAPTOR-C19). - Brian D Nicholson; Philip J Turner; Thomas R Fanshawe; Alice J Williams; Gayatri Amirthalingam; Sharon Tonner; Maria Zambon; Richard Body; Kerrie Davies; Rafael Perera; Simon de Lusignan; Gail N Hayward; et al. (PLoS ONE)
Background and objective Point-of-care lateral flow device antigen testing has been used extensively to identify individuals with active SARS-CoV-2 infection in the community. This study aimed to evaluate the diagnostic accuracy of two point-of-care tests (POCTs) for SARS-CoV-2 in routine community care. Methods Adults and children with symptoms consistent with suspected current COVID-19 infection were prospectively recruited from 19 UK general practices and two COVID-19 testing centres between October 2020 and October 2021. Participants were tested by trained healthcare workers using at least one of two index POCTs (Roche-branded SD Biosensor Standard™ Q SARS-CoV-2 Rapid Antigen Test and/or BD Veritor™ System for Rapid Detection of SARS-CoV-2). The reference standard was laboratory triplex reverse transcription quantitative PCR (RT-PCR) using a combined nasal/oropharyngeal swab. Diagnostic accuracy parameters were estimated, with 95% confidence intervals (CIs), overall, in relation to RT-PCR cycle threshold and in pre-specified subgroups. Results Of 663 participants included in the primary analysis, 39.2% (260/663, 95% CI 35.5% to 43.0%) had a positive RT-PCR result. The SD Biosensor POCT had sensitivity 84.0% (178/212, 78.3% to 88.6%) and specificity 98.5% (328/333, 96.5% to 99.5%), and the BD Veritor POCT had sensitivity 76.5% (127/166, 69.3% to 82.7%) and specificity 98.8% (249/252, 96.6% to 99.8%) compared with RT-PCR. Sensitivity of both devices dropped substantially at cycle thresholds ≥30 and in participants more than 7 days after onset of symptoms. Conclusions Both POCTs assessed exceed the Medicines and Healthcare products Regulatory Agency target product profile's minimum acceptable specificity of 95%. Confidence intervals for both tests include the minimum acceptable sensitivity of 80%. In symptomatic patients, negative results on these two POCTs do not preclude the possibility of infection. Tests should not be expected to reliably detect disease more than a week after symptom onset, when viral load may be reduced. Registration ISRCTN142269.